Daya Hambat Ekstrak Air Kopi Robusta (Coffea Canephora) terhadap Bakteri Propionibacterium Acnes - Ilham Mauludin; Hendro Sudjono Yuwono; Dicky Santosa (Bandung Conference Series: Medical Science, 2022)
Abstract. The prevalence of acne vulgaris in Indonesia as much as 80-85% is teenagers peak at 15-18 years. Topical and oral antibiotics suppressed the activity of Propionibacterium acnes in acne. It can cause resistance and result in therapy failure. The purpose was to determine the antibacterial effect of Robusta Coffee (Coffea canephora) aqueous extract. This research is a descriptive experimental study using isolates of bacteria P. acnes ATCC 11827, taken from the Unisba Pharmaceutical Microbiology Lab, with the method of disc diffusion and adapted to the standard 0.5 McFarland. Six research groups were comprised four concentrations of aqueous extract. It is namely 25%, 50%, 75%, and 100%. Positive control (erythromycin antibiotics), and negative control (aqua des) which was then incubated for 24 hours at 37°C and it measured the diameter of the inhibition zone in millimeters. The results showed that the largest inhibition zone at 100% concentration was 7.90 mm. Of 50% and 25% were not detected. The erythromycin inhibition zone formed 23.99 mm. Coffee can overcome bacterial infections that cause acne because it can produce H₂O₂ and create a hyperosmotic solution atmosphere. This study concludes that robusta coffee water extract can inhibit the growth of bacteria P. acne, but the inhibition zone is lower than the erythromycin inhibition zone. Abstrak. Prevalensi akne vulgaris di Indonesia sebanyak 80-85% adalah usia remaja puncaknya pada usia 15-18 tahun. Penggunaan antibiotik untuk menekan aktivitas Propionibacterium acne pada jerawat, dapat menyebabkan resistensi. Tujuan penelitian ini adalah mengetahui daya hambat ekstrak air Kopi Robusta (Coffea canephora) pada media agar kultur Propionibacterium acne. Penelitian ini merupakan studi deskriptif eksperimental in vitro menggunakan isolat bakteri P. acnes, yang diambil dari Lab Mikrobiologi Farmasi Unisba, dengan metode disc diffusion dan disesuaikan dengan standar 0,5 McFarland. Terdapat enam kelompok penelitian terdiri dari empat konsentrasi ekstrak air yaitu 25%, 50%, 75% dan 100%, kontrol positif (antibiotik eritromisin), dan kontrol negatif (cairan akuades) yang selanjutnya diinkubasi selama 24 jam pada suhu 37℃. Zona hambat diukur diameternya dalam milimeter. Hasil penelitian menunjukan zona hambat pada konsentrasi 100% yaitu 7,90 mm, sedangkan pada konsentrasi 50% dan 25% tidak terdeteksi. Pada eritromisin zona hambat terbentuk 23,99 mm. Kopi dapat mengatasi infeksi bakteri penyebab jerawat karena menghasilkan H₂O₂ dan menciptakan larutan hiperosmotik. Kesimpulan ekstrak air kopi robusta dapat menghambat pertumbuhan bakteri P. acne, namun lebih rendah dibandingkan zona hambat eritromisin.